Analisis Eksperimental Pengaruh Variasi Ketinggian Dome Piston terhadap Performa Mesin 4-Tak - Mahendra, Esa Ramdhan Ardi; Mara, I Made; Sutanto, Rudy (CV. IRA PUBLISHING, 2025)
Internal combustion engines remain the primary power source in transportation by converting fossil fuel energy into mechanical energy. This study examines the effect of piston dome height variations (1 mm, 3 mm, and 5 mm) on the performance of a 4-stroke 87.70 cc engine. A quantitative method was used with a rope brake dynamometer to measure torque, adequate power, fuel consumption, and SFCe, effective at engine speeds ranging from 2000 to 5000 rpm. The highest torque and power were recorded at 4000 rpm, the highest fuel consumption at 5000 rpm, and the highest SFCe at 2000 rpm for all dome height variations. As piston dome height increases, combustion chamber volume decreases, leading to lower compression ratios and reduced combustion efficiency. Therefore, piston design should be aligned with the intended focus on either efficiency or performance.